2021
DOI: 10.1186/s12904-021-00740-3
|View full text |Cite
|
Sign up to set email alerts
|

Hospice care providers experiences of grappling with medical assistance in dying in a hospice setting: a qualitative descriptive study

Abstract: Background Rapid implementation of Medical Assistance in Dying (MAiD) across care settings has challenged providers and organizations, including hospices, to develop and implement new modes of practice. The aim of this study was to examine the effects that legalization of MAiD has had on hospice care provider roles within the non-provider context. Methods Eight in-depth semi-structured interviews were conducted and a qualitative descriptive approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
12
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 25 publications
5
12
0
1
Order By: Relevance
“…Our results also extend previous findings that a hospice’s response to legalisation can create challenges for a hospice and its staff 8 10. Specifically, our results aligned with and elaborated those of Freeman et al that demonstrated how the separation of MAID and hospice care can lead to communication issues among staff, and a feeling among hospice staff of being disconnected from the patient’s care surrounding MAID 10. These feelings were most pronounced when a patient was transferred off-site to receive MAID, with staff in our study reporting distress with this occurrence 10.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Our results also extend previous findings that a hospice’s response to legalisation can create challenges for a hospice and its staff 8 10. Specifically, our results aligned with and elaborated those of Freeman et al that demonstrated how the separation of MAID and hospice care can lead to communication issues among staff, and a feeling among hospice staff of being disconnected from the patient’s care surrounding MAID 10. These feelings were most pronounced when a patient was transferred off-site to receive MAID, with staff in our study reporting distress with this occurrence 10.…”
Section: Discussionsupporting
confidence: 90%
“…Our results provide insight into the challenges and opportunities MAID brings to Canadian hospices. Like Freeman et al , our findings highlight that the introduction of MAID has left many hospice staff struggling to reconcile patient requests for MAID with their own beliefs regarding hospice facilities and hospice care 10. Since its inception in 1967, the modern hospice movement has been rooted in providing a certain dying experience, in which the patient’s end-of-life needs are addressed through holistic comfort care, enabling the patient to find meaning as they face their upcoming death alongside their family and friends 18–20.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations